-27=0.6x

Simple and best practice solution for -27=0.6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=0.6x equation:


Simplifying
-27 = 0.6x

Solving
-27 = 0.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6x' to each side of the equation.
-27 + -0.6x = 0.6x + -0.6x

Combine like terms: 0.6x + -0.6x = 0.0
-27 + -0.6x = 0.0

Add '27' to each side of the equation.
-27 + 27 + -0.6x = 0.0 + 27

Combine like terms: -27 + 27 = 0
0 + -0.6x = 0.0 + 27
-0.6x = 0.0 + 27

Combine like terms: 0.0 + 27 = 27
-0.6x = 27

Divide each side by '-0.6'.
x = -45

Simplifying
x = -45

See similar equations:

| 63700/35 | | 8X+9=-7-8(x+4) | | -3x-5(1+3x)=6-7x | | ((y^(5/2))*(y^(-1/2)))/(y^(1/3)) | | 3(x-5)+1=0 | | 2v+24=-2(4+v) | | 8n+3=34 | | -243=-6x-5(1-8x) | | 7x^3/2=-14 | | -3(3+7n)=-93 | | 12-17x=15x | | N^2-8=41 | | -1/12=X-5/9 | | (5y-2)(y+3)=0 | | 6z+4z=9z-8 | | -4/9y=-1/2 | | 10n/10m=10n-m | | (6y/12)=1 | | x^2+8x+3=F(X) | | 10a^2-7a=1 | | 6n^2=21-2n | | 3r^2-42=11r | | 8x-3+7x=7x+5-9x | | 2xy^2-7ay+3xy-3y=0 | | 8n^2=-6n+11 | | 6X+17Y=2000 | | (2x+6)=2 | | x^8=24 | | 1/2x-5=1/2x-4 | | C/4-11=3 | | P^2+2p=15 | | 12y^3+6y^2-3y=0 |

Equations solver categories